Peran Dukungan Guru dan Efikasi diri Terhadap Keterlibatan dengan Siswa MTS Tahfizhil Quran - Nadiyah Zahra Lubis; Pulung Sumantri; Latifah Hanum; Hadiani Fitri (Universitas Islam Sumatera Utara, 2022)
Precisely, this study was highlighted seeing the association between instructor support, self-feasibility, and student responsibility. The general population in this assessment is the students as a rule, amounting to 400 students, and the model was 186 students, where the model was taken using proportionately isolated sporadic testing. Item second relationship, information examination, and scale and documentation information assortment techniques are totally recorded. The results showed that: There was an immense positive association between teacher support and student responsibility, with a coefficient (rxy) = 0,481 and a p worth of 0.0020.050, with a responsibility of educator sponsorship to student responsibility of 25,7%. There was an enormous positive association between self-feasibility and student responsibility, with a coefficient of regard (rxy) = 0,512 and p = 0.0000.050. Self-viability affects understudy commitment. 3) There was a positive and colossal connection between teacher sponsorship and self-feasibility and student responsibility, with a coefficient regard (rxy) of 0,562 and a p worth of 0.000 0.050, with the responsibility of educator support and self-reasonability sponsorship to student responsibility of 32.7%.